Micro- and Macroelement Contents of Edible Wild Growing Mushrooms in Artvin Province of Turkey - Sesli, Ertugrul; Tuzen, Mustafa (Asian Journal of Chemistry, 2010)
Fruiting bodies of Armillaria mellea, Boletus edulis, Bovista plumbea, Cantharellus cibarius var. cibarius, Cantharellus tubaeformis, Hydnum repandum, Laccaria laccata, Lactarius piperatus, Lactarius volemus, Lactarius circellatus, Lentinellus cochleatus, Lepista nuda, Lycoperdon pyriforme, Ramaria flava, Russula delica, Tricholoma imbricatum and Tricholomopsis rutilans were collected from oriental spruce stands of Artvin province in Turkey. Micro- and macroelement contents in the fruiting bodies were determined by atomic absorption spectrometry after microwave digestion. The results were (as mg/kg) 0.23–1.59 silver, 20.6–79.5 aluminium, 0.23–2.74 cadmium, 0.55–2.72 lead, 23.9–87.8 copper, 139–895 iron, 9.1–93.2 manganese, 38.8–194 zinc, 415–1503 sodium, 22270–51455 potassium, 508–3267 calcium and 674–1819 magnesium.